Adhesion formation after intracapsular myomectomy with or without adhesion barrier - Tinelli, Andrea; Malvasi, Antonio; Guido, Marcello; Tsin, Daniel Alberto; Hudelist, Gernot; Hurst, Brad; Stark, Michael; Mettler, Liselotte (Fertility and sterility, 2011)
To show the prevention of adhesion formation by placing an absorbable adhesion barrier after intracapsular myomectomy. Prospective blinded observational study. University-affiliated Hospitals. Patients ≥18 years old with single or multiple uterine fibroids removed by laparoscopic or abdominal intracapsular myomectomy. A total of 694 women undergoing laparoscopic or abdominal myomectomy were randomized for placement of oxidized regenerated cellulose absorbable adhesion barrier to the uterine incision or for control subjects without barriers. The presence of adhesions was assessed in 546 patients who underwent subsequent surgery. The primary and secondary outcomes of the analysis were the presence and severity of adhesions for four groups: laparotomy with barrier, laparotomy without barrier, laparoscopy with barrier, and laparoscopy without barrier. There was a higher rate of adhesions in laparotomy without barrier (28.1%) compared with laparoscopy with no barrier (22.6%), followed by laparotomy with barrier (22%) and laparoscopy with barrier (15.9%). Additionally, the type of adhesions were different, filmy and organized were predominant with an adhesion barrier, and cohesive adhesions were more common without an adhesion barrier. Oxidized regenerated cellulose reduces postsurgical adhesions. Cohesive adhesions reduction was noted in laparoscopy.